AGE DYNAMICS OF THE MAXIMUM ALACTATE POWER OF HIGHLY QUALIFIED HOCKEY PLAYERS - Shishkov, I.Yu.; Furaev, A.N.; Rybakov, V.A. (Theory and Practice of Physical Culture, 2022)
Abstract Objective of the study was to evaluate the dynamics of maximum alactic power (MAP) as the main indicator of the speed-strength fitness of hockey players and to identify its relationship with the age of athletes. Methods and structure of the study. The work was carried out on the example of hockey players (n=11, field hockey), who underwent regular testing for 14 years. To assess this indicator in laboratory studies, a modified Wengate test was used. Results and conclusions. Testing of the index of maximum alactic power (MAP) of highly qualified field hockey players conducted over 14 years allows us to speak about the dynamics of an increase in the level of speed-strength fitness of the muscles of the lower extremities in the process of ontogenesis in all the studied athletes, which is confirmed by the results of regression (an increase in R2 from 0.51 to 0.80) and correlation (p<0.01) analyses. Adequate construction of the training process for athletes under the age of 40 contributes to an increase in the indicator of maximum alactic power.